Beam instability caused by stochastic plasma density fluctuations - Buts, A.V.; Chatskaya, V.A.; Tyrnov, O.F. (Вопросы атомной науки и техники, 2000)
Beam instability in a plasma with the density varying stochastically with respect to space or time is investigated. In case of spatial variations, the system of equations in moments of arbitrary order is obtained and analyzed. It is shown that each moment in the sequence grows faster than the preceding one. As a result an intermittent character of development of the instability arises, and the appearance of some critical length within which the amplification of a regular signal is yet possible. In case of temporal variations, the maximum time interval of signal destitution due to fluctuation interference is estimated.